The clinical values of dysregulated DNA methylation and demethylation intermediates in acute lymphoblastic leukemia. Issue 1 (1st January 2019) - Cao, Lin-Lin; Liu, Hangqi; Yue, Zhihong; Pei, Lin; Wang, Hui; Jia, Mei
ABSTRACT: Objectives: DNA methylation is a well-known epigenetic modification, and it can be iteratively oxidized to 5-hydroxymethylcytosine (5-hmC), 5-formylcytosine (5-fC) and 5-carboxylcytosine (5-caC). Acute lymphoblastic leukemia (ALL) is a severe hematological disease, and it is essential to find out new biomarkers to better diagnose and cure ALL due to the development of chemo-resistance and low cure rate in adult ALL. This study aims to describe the role of global methylation and demethylation intermediates in ALL. Methods: The levels of global methylation and its oxidation products in the peripheral blood (PB) of ALL patients and healthy controls were determined by Enzyme-Linked Immunosorbent Assay (ELISA). Results: In this study, we described that global 5-mC, 5-hmC and 5-fC levels were dysregulated in ALL, and they were associated with clinical characteristics and genetic abnormalities of ALL patients. Interestingly, 5-mC and 5-hmC were closely related to inflammation, and the levels of 5-hmC were inversely correlated with C-Reactive protein (CRP) and ferritin. Finally, 5-mC and 5-hmC were associated with complete remission (CR), and 5-hmC was revealed as an independent prognostic indicator for ALL. Conclusion: This study described a novel role for global methylation and demethylation intermediates in ALL detection and prognosis, and provided new clue to distinguish high-risk patients and improve the curative effect on ALL patients.